THE INFLUENCE OF TECHNOLOGY AS A SUPPORTER OF EDUCATION, ESPECIALLY IN ENGLISH LESSONS - Batubara, Olina Putri; Silitonga, Cindy Tania Mutiara; Sipayung, Sabarni Rodearni (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This research aims to find the advances in technology today. Technology has a big influence in the world of education. Today’s sophisticated technology has become something important to influence the teaching and learning process. One of them is in English subject. This is because the use of English is no longer just for greeting, but also for other needs to support an activity. English is an international language, which everyone is required to understand. In the world of education, students’ lack of interest in these subjects makes English lessons increasingly difficult to master. Therefore, assistance using advanced technology is needed to attract the attention of students in the teaching and learning process